A rare case of flexor tenosynovitis due to tuberculosis in hand and wrist: A case report [Vzácný případ tuberkulózní tenosynovialitidy ruky a zápĕstí: Kazuistika] - (:unkn) unknown (Galen s.r.o., 2021)
Tuberculosis (TB) is still a worldwide problem. We present a case of flexor tenosynovitis due to tuberculosis in the hand and wrist. A 42-year-old man presented to the outpatient clinic with a 2-year history of a slowly growing mass over the volar aspect of the left wrist. His MRI showed multiple rice bodies in the wrist and hand. An open biopsy was performed. Pathology specimens showed granulomatous lesions with central necrosis. The purified protein derivative (PPD) test was positive. In this case, granulomatous lesions with central necrosis, rice bodies, and positive PPD test confirmed the diagnosis of TB in the wrist and hand. There was no other concurrent evidence of TB elsewhere. Antituberculosis chemotherapy was commenced. Tuberculous tenosynovitis of the wrist and hand is very rare. The tuberculous tenosynovitis should be kept in mind as an infectious agent when patients are presenting with atypical clinical. © Česká společnost.
Keywords: Flexor tenosynovitis; Hand; Rice bodies; Tuberculosis; Wrist